2014
DOI: 10.1002/j.2161-1920.2014.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Concerns of Elementary Teachers: Stress, Job Satisfaction, and Occupational Commitment

Abstract: This study examines the vocational concerns of 185 elementary teachers. Participants were classified based on their perceptions of the magnitude of their classroom demands and resources. These groupings were then examined for differences in teachers' personal coping resources, job satisfaction, and occupational commitment. Results indicated that teachers classified as perceiving high classroom demand vis-à-vis classroom resources reported lower personal coping resources, less job satisfaction, and more plans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…The mounting evidence indicates different groups of teachers may have distinctive attitudes towards job commitment, job satisfaction, and burnout. Specifically, teachers in the Demands group are less satisfied with their jobs (McCarthy et al., ), more likely to leave the teaching profession (McCarthy, Kerne, Calfa, Lambert, & Guzmán, ), and more likely to suffer from burnout symptoms (McCarthy, Lambert, O'Donnell, & Melendres, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mounting evidence indicates different groups of teachers may have distinctive attitudes towards job commitment, job satisfaction, and burnout. Specifically, teachers in the Demands group are less satisfied with their jobs (McCarthy et al., ), more likely to leave the teaching profession (McCarthy, Kerne, Calfa, Lambert, & Guzmán, ), and more likely to suffer from burnout symptoms (McCarthy, Lambert, O'Donnell, & Melendres, ).…”
Section: Methodsmentioning
confidence: 99%
“…Teaching is one of the most stressful occupations (Gold & Roth, ; Johnson et al., ; Shen et al., ) in both western countries (Kyriacou, ; Lambert & McCarthy, ; McCarthy, Lambert, Lineback, Fitchett, & Baddouh, ; McCarthy, Lambert, & Reiser, ) and eastern countries, such as Singapore (Chan, Lai, Ko, & Boey, ), Malaysia (Masilamani et al., ), and China (Wang et al., ; Yong & Yue, ; Zhang, Bian, & Dong, ). According to one prominent stress theory, namely the transactional model of stress and coping, stress occurs as a result of an imbalance between perceived demands and perceived capability or resources to cope with those demands (Lazarus & Folkman, ).…”
Section: Classroom Appraisal Of Resources and Demandsmentioning
confidence: 99%
“…Similarly, teachers’ perceptions of school climate affected their stress and job satisfaction (Butt et al., ) and burnout (Grayson & Alvarez, ). McCarthy and colleagues (McCarthy, Lambert, & Reiser, ) found that teachers who perceived high classroom demand and low classroom resources reported less job satisfaction and higher turnover plans.…”
Section: Teacher Stress and School Contextsmentioning
confidence: 99%
“…Reward system, together with work period (McCarthy, Lambert & Reiser, 2014), classroom demand (McCarthy et al, 2014) and school status (Buka & Bilgic, 2010) made up the organizational-support extrinsic factor of organizational commitment. Recent empirical studies, such as Joo, Lee and Jung (2012), Vansteenkiste dan De Witte (2002) and Chepkwony (2014), found out that reward system enhance commitment as well as motivation and morale.…”
Section: Reward System As Organizational-support Extrinsic Factormentioning
confidence: 99%